The Formation of the Core of the Hirsch Index of the Pedagogical Universities of Ukraine: The Gender Features - Akbash, K. S.; Pasichnyk, N. O.; Rizhniak, R. Ya.; Baranchenko, Ye. (Statistics of Ukraine, 2023)
In the article, the authors disclosed the results of the study that was conducted with the aim of determining the gender characteristics of the groups of the authors of articles that were included in the core of the Hirsch index for each pedagogical university of Ukraine (according to the SciVerse Scopus database) as well as to analyze the influencing factors on the formation of the core of the Hirsch index of these universities in the context of the gender division. For this purpose, one-factor variance analysis and elementary methods of statistical analysis were used - a calculation of percentage ratios and determination of gender asymmetry indices. The gender analysis of the group of authors whose articles were included in the h-index core of each university showed that in the presence of the general gender parity in the gender groups of authors whose articles are indexed by the Scopus database, there is a gender asymmetry between the gender groups of authors of articles from the core in favor of the male authors. The same tendency occurs between the gender groups of authors, whose articles were included in the core of the h-index of the combined list of all the pedagogical universities of Ukraine: both for the ratio of the groups of authors of articles, and for the ratio of contributions of the groups to the core. As a result of a series of univariate variance analyzes of the influence of the external factors on the formation of the Hirsch index core, a significant gender difference was revealed when analyzing the following factors: presence/absence of publication funding (articles that have funding have a much higher citation rate), publication quartile (articles placed in publications of the first quartile, are cited much more often) and the age of the article (the older the article, the higher its citation index). At the same time, factors such as the number of authors of the article and the type of access to the article did not influence the formation of the core of the h-index of the pedagogical higher educational institutions. Moreover, only one factor (the availability of access to the article) can be characterized as a gender parity. On the contrary, there is an obvious gender difference in the distribution of the number of authors in the articles, the availability of funding for the publication, the “age” of the article, and in the distribution of articles by the publications of the first two quartiles.